1980
DOI: 10.1002/ajh.2830080407
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of SV40 T‐antigen expression in vitro to disorders of bone marrow function

Abstract: Skin fibroblasts from patients with a variety of hematologic disorders were infected with SV40 virus in vitro in attempts to discover the reason for increased susceptibility of Fanconi anemia cells to this transforming virus. The proportion of skin fibroblasts expressing SV40 T-antigen by immunofluorescent methods was elevated in 12 patients with Fanconi anemia and in seven of nine obligate heterozygous relatives. Elevated expression was also observed in three patients with other hematological disorders at hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1981
1981
2013
2013

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Several investigations have reported that FA fibroblasts are particularly sensitive to transformation by SV40 T-Ag (Todaro et al, 1966;Dosik et al, 1970;Lubiniecki et al, 1980). This phenomenon is directly linked to the primary defect in these cells since correction of FA-C cells by transduction with FANCC has been shown to reduce their transformation potential (Liu et al, 1996).…”
Section: Sv40 Transformation and Famentioning
confidence: 99%
“…Several investigations have reported that FA fibroblasts are particularly sensitive to transformation by SV40 T-Ag (Todaro et al, 1966;Dosik et al, 1970;Lubiniecki et al, 1980). This phenomenon is directly linked to the primary defect in these cells since correction of FA-C cells by transduction with FANCC has been shown to reduce their transformation potential (Liu et al, 1996).…”
Section: Sv40 Transformation and Famentioning
confidence: 99%
“…In cell transformation and tumorigenesis, the SV40 large antigen (LT) oncoprotein targets and inactivates the functions of key cellular products, such as the tumor suppressor p53 and the pRB family proteins. LT may also lead to transformation by inducing point mutations and chromosomal alterations, suggesting that the SV40 transforming properties depend on its ability to perturb tumor suppressor pathways, apoptotic processes and cell growth [10] , [11] .…”
Section: Introductionmentioning
confidence: 99%